(untitled) (Comparative & International Education Series, 2022)
As the theater doors swing open, the audience members rush in to find their seats. The theater is filled with side-stepping and jostling until everybody has settled into their place. Quickly, silence falls over the crowd like a dispersing mist. All the lights turn off and the curtain rises slowly. A female student from South Korea, who has rosy cheeks and dark brown eyes complemented by shining, premature gray hair, walks toward center stage. Lights turn on one by one, following her footsteps, and the audience holds its collective breath. The student, standing tall at the center, looks around as if searching the crowd for someone. As she clears her voice, her Coke-bottle glasses slip down her flat nose and she pushes them back up. She musters up the courage to tell the audience about a friend whose unconditional kindness opened her eyes to seeing the world as a good place to live in again. She now begins her story…